On the Role of Last Closed Drift Shell Dynamics in Driving Fast Losses and Van Allen Radiation Belt Extinction. Issue 5 (16th May 2018) - Olifer, L.; Mann, I. R.; Morley, S. K.; Ozeke, L. G.; Choi, D.
Abstract: We present observations of very fast radiation belt loss as resolved using high time resolution electron flux data from the constellation of Global Positioning System (GPS) satellites. The time scale of these losses is revealed to be as short as ∼0.5–2 hr during intense magnetic storms, with some storms demonstrating almost total loss on these time scales and which we characterize as radiation belt extinction. The intense March 2013 and March 2015 storms both show such fast extinction, with a rapid recovery, while the September 2014 storm shows fast extinction but no recovery for around 2 weeks. By contrast, the moderate September 2012 storm which generated a three radiation belt morphology shows more gradual loss. We compute the last closed drift shell (LCDS) for each of these four storms and show a very strong correspondence between the LCDS and the loss patterns of trapped electrons in each storm. Most significantly, the location of the LCDS closely mirrors the high time resolution losses observed in GPS flux. The fast losses occur on a time scale shorter than the Van Allen Probes orbital period, are explained by proximity to the LCDS, and progress inward, consistent with outward transport to the LCDS by fast ultralow frequency wave radial diffusion. Expressing the location of the LCDS in L *, and not model magnetopause standoff distance in units of R E, clearly reveals magnetopause shadowing as the cause of the fast loss observed by the GPS satellites. Key Points: GPS electron flux data reveal very fast radiation belt losses, which can be as short as  0.5–2 hr during radiation belt extinction events Dynamics of the last closed drift shell mirrors the observed loss in studied storms indicating magnetopause shadowing was the dominant cause Electron populations with different energies show similar loss patterns indicating an inward loss propagation, with fast outward transport